IMPLEMENTASI LVEP (LIVING VALUE EDUCATION PROGRAM) DI MADRASAH IBTIDAIYAH MANBAUL ULUM MOJOPURO GEDE BUNGAH GRESIK - Faizin, Moh. (Journal Of Islamic Elementary School (JIES), 2019)
LVEP (Living Values ??Education Program) is a valuable educational program that has an international network that offers practical training and methods for teachers, facilitators, and even parents and child assistants. LVEP helps provide opportunities for children and young people to explore and develop universal values, social and emotional skills, intrapersonal and interpersonal. LVEP also helps students to explore and develop their personal values ??in solving everyday life problems. The purpose of this value education is to live up to what already exists, and provide a tool to understand what the impact of an action is on oneself, others and the community and improve leadership abilities based on those values. The formulation of the problem from this study are: (1) What is meant by LVEP (Living Value Education Program) in Islamic education institutions? (2) What are the values ??contained in the LVEP (Living Value Education Program) in Islamic education institutions? (3) How is the implementation of LVEP (Living Value Education Program) in the Madrasah Ibtidaiyah Manbaul Ulum Mojopuro Gede Bungah Gresik? The students in the madrasa are always encouraged to use the local culture by integrating it into their daily activities and curriculum. In the LVEP implementation series, reflective activity and visualization help students to use their creativity and talents. Communication activities teach them to implement peaceful social skills. Art activities, songs, and movements inspire students to express themselves while directly experiencing the value being taught. Game activities invite students to think and have fun, namely during discussions so they are able to explore different attitudes and behaviors. Other activities stimulate awareness of personal and social responsibility and social justice. The whole set of activities also emphasizes self-esteem development and tolerance. Reasons for Madrasah Ibtidaiyah Manbaul Ulum Mojopuro Gede Bungah Gresik make LVEP the flagship program because LVEP activities include values ??of peace, respect, compassion, tolerance, honesty, humility, cooperation, happiness, responsibility, simplicity, freedom, and unity.